Perceptions of joint pain and feeling well in older people who reported being healthy: a qualitative study - Grime, Janet (Royal College of General Practitioners, 2010)
BACKGROUND: Older people often view osteoarthritis as a part of normal ageing and see themselves as healthy despite painful joints. Professionals have mixed views about this. One concern is that seeing osteoarthritis as a result of ‘wear and tear’ leads to restricting exercise in order to avoid further wear. AIM: To explore lay perceptions of wellness and joint pain, and their implications for consulting healthcare professionals and taking exercise. DESIGN OF STUDY: Qualitative, longitudinal study. SETTING: General practice in the North Midlands. METHOD: Semi-structured interviews with 27 older people who reported a joint problem but rated themselves as healthy. Diary sheets were sent for 11 consecutive months to record changes in health and circumstances. Thematic data analysis was facilitated by NVivo 8. RESULTS: A key element of wellness was being able to continue with everyday roles and activities. ‘Wear and tear’ was used to categorise arthritis that is a normal part of old age. New joint symptoms that came on suddenly and severely were not necessarily attributed to ‘wear and tear’ arthritis, and were likely to lead to a professional consultation. Physical activity was not restricted to prevent further wear of affected joint(s). Keeping joints mobile was important in order to maintain independence. CONCLUSION: Professionals should explore patients' ideas and concerns about their joint problem, in order to individually tailor explanations and advice. Patients are likely to be receptive to recommendations that promote independence, but advice needs to be set into patients' existing ways of living and coping with joint pain.